Depletion of lncRNA MEG3 Ameliorates Imatinib-Induced Injury of Cardiomyocytes via Regulating miR-129-5p/HMGB1 Axis - Peng Tang; Jinjian Zhou; Huagang Liu; Shenglan Mei; Kai Wang; Hao Ming (Analytical Cellular Pathology)
Imatinib is a classical targeted drug to treat chronic myeloid leukemia (CML). However, it shows cardiotoxicity, which limits its clinical application. Long noncoding RNA (lncRNA) maternally expressed gene 3 (MEG3) shows proapoptotic properties in human cells. This study is performed to investigate whether targeting MEG3 can attenuate imatinib-mediated cardiotoxicity to cardiomyocytes. In this work, H9c2 cells were divided into four groups: control group, hypoxia group, hypoxia + imatinib, and hypoxia + imatinib + MEG3 knockdown group. MEG3 and microRNA-129-5p (miR-129-5p) expression levels were detected by the quantitative real-time PCR (qRT-PCR). The viability and apoptosis of H9c2 cells were then evaluated by cell counting kit-8 (CCK-8), flow cytometry, and TUNEL assays. The targeting relationships between MEG3 and miR-129-5p, between miR-129-5p and high-mobility group box 1 (HMBG1), were validated by dual-luciferase reporter assay and RNA Immunoprecipitation (RIP) assay. The protein expression level of HMGB1 was detected by western blot. It was revealed that, Imatinib-inhibited cell viability and aggravated the apoptosis of H9c2 cells cultured in hypoxic condition, and MEG3 knockdown significantly counteracted this effect. MiR-129-5p was a downstream target of MEG3 and it directly targeted HMGB1, and knockdown of MEG3 inhibited HMGB1 expression in H9c2 cells. In conclusion, targeting MEG3 ameliorates imatinib-induced injury of cardiomyocytes via regulating miR-129-5p/HMGB1 axis.